2004
DOI: 10.1017/s0031182003004700
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma marginale(Rickettsiales: Anaplasmataceae): recent advances in defining host–pathogen adaptations of a tick-borne rickettsia

Abstract: The tick-borne intracellular pathogen Anaplasma marginale (Rickettsiales: Anaplasmataceae) develops persistent infections in cattle and tick hosts. While erythrocytes appear to be the only site of infection in cattle, A. marginale undergoes a complex developmental cycle in ticks and transmission occurs via salivary glands during feeding. Many geographic isolates occur that vary in genotype, antigenic composition, morphology and infectivity for ticks. In this chapter we review recent research on the host-vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
229
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(240 citation statements)
references
References 69 publications
3
229
0
8
Order By: Relevance
“…In Portugal and Spain, R. bursa is a proven vector of A. marginale and the infection of cattle, known as bovine anaplasmosis, caused by this pathogen has been already reported (Caeiro, 1999;de la Fuente et al, 2004a;Kocan et al, 2004). Bovine anaplasmosis is now known to be endemic in tropical and subtropical regions worldwide, causing substantial economic losses to cattle industries (Kocan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In Portugal and Spain, R. bursa is a proven vector of A. marginale and the infection of cattle, known as bovine anaplasmosis, caused by this pathogen has been already reported (Caeiro, 1999;de la Fuente et al, 2004a;Kocan et al, 2004). Bovine anaplasmosis is now known to be endemic in tropical and subtropical regions worldwide, causing substantial economic losses to cattle industries (Kocan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…and Ixodes spp. (Uilenberg, 1995;De Waal et al, 2000;Jongejan and Uilenberg, 2004;Kocan et al, 2004). Tick transmissibility of Anaplasma is complex and ranges from very efficient transmission to non-transmission related to both Anaplasma strains as well as species of tick (Ueti et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Anaplasmosis has been reported in different regions of Morocco (Verhulst et al, 1983;Sahibi et al, 1998b), but it has a perceived lower incidence compared with theileriosis and babesiosis. Although, severe economic losses have been reported due to anaplasmosis outbreaks in several parts of the world (Herrero et al, 1998;Kocan et al, 2000Kocan et al, , 2004Grisi et al, 2002;Jongejan and Uilenberg, 2004), no specific disease outbreak of A. marginale in cattle has been reported in Morocco and the only epidemiological studies of anaplasmosis reported previously were conducted more than a decade ago (Sahibi et al, 1998b).…”
Section: Introductionmentioning
confidence: 99%
“…A infecção é causada pelo desenvolvimento e multiplicação de Babesia spp. e A. marginale nas células sangüíneas e tem como sinais clínicos febre, anemia, icterícia (mais intensa e comum na anaplasmose), hemoglobinúria (na babesiose), parada ou redução da ruminação, sinais nervosos (característicos da babesiose por B. bovis, o mais virulento dos três agentes), anorexia e prostração (Dreher et al 2005, Kocan et al 2004, Souza et al 2000.…”
Section: Introductionunclassified